Risk of lymph node metastasis and recommendations for elective nodal treatment in squamous cell carcinoma of the nasal cavity and maxillary sinus: a SEER analysis. (2nd October 2016) - Ahn, Peter H.; Mitra, Nandita; Alonso-Basanta, Michelle; Palmer, James N.; Adappa, Nithin D.; O'Malley, Bert W.; Rassekh, Christopher; Chalian, Ara; Cohen, Roger B.; Lin, Alexander
Abstract: Background: Risk of nodal involvement in patients with squamous cell carcinomas (SCC) of the nasal cavity and maxillary sinus has not been well defined, especially by risk factors beyond local T-stage. Additional criteria defining patients at highest risk, as well as specific nodal levels at highest risk, has been limited in small retrospective series. We describe a population-based assessment of specific nodal involvement in this group. Material and methods: The Surveillance, Epidemiology and End Results (SEER) database from 2004 to 2010 identified 1283 eligible patients with SCC of the nasal cavity or maxillary sinus. Neck involvement and individual nodal level involvement at presentation were assessed, and comparison made with a contemporaneous cohort of patients with a borderline clinically significant risk of nodal involvement and recurrence. Results: Among 1283 patients, 182 (14.2%) had nodal involvement at presentation (4–27% by site and local extension). T-stage alone was associated with higher rates of nodal involvement in maxillary sinus SCC, while higher T-stage and size >2 cm were associated with higher rates of nodal involvement in nasal cavity SCC on multivariable analysis. Facial nodes and cervical nodes at levels 1 and 2 have the highest rates of involvement in T4a nasal cavity SCC, whereas nodal levels 1, 2, and/or 3 have the highest rates of involvement in T2 or higher maxillary sinus SCC when compared with a clinical reference standard. Conclusion: In this population-based study, there are high rates of initial nodal involvement when stratified by local extent determined by T-stage in nasal cavity SCC and maxillary sinus SCC, and independently by size in nasal cavity SCC. Involvement of the facial and nodal levels 1–3 varies depending on site and local extent of tumor involvement. These observations may help guide treatment decision making in the inclusion of and extent of elective nodal treatment fields.